Pentingnya Klasifikasi Customer Sebelum Melakukan Perancangan Strategi Digital Marketing - Iasa Nur Firdausi; Siti Ning Farida (Jurnal Nusantara Berbakti, 2023)
The failure of the digital marketing campaign at PT Lentera Alam Nusantara is the author's background for researching the best solutions before designing a digital marketing strategy. This research journal aims to measure and prove how important customer classification is as a basis for designing digital marketing strategies in the hope of minimizing campaign failures. The research was conducted descriptively using a qualitative approach to gather information and provide a detailed description of the phenomenon. The research findings prove that there is a significant positive influence on the results of strategy implementation after customer classification. Thus it can be interpreted that the author's hypothesis about the importance of customer classification before designing a digital marketing strategy at PT Lentera Alam Nusantara can be proven by the results of the research.